Somewhere 2017-2023 - Campany, David 1967-; Goulding, Matt; Stoppard, Lou 19XX- (Loose Joints Publishing, 2023)
Sam Youkilis's immediate and generous indexing of everyday life reaches across space and time in his debut monograph – a 528-page typology of human experience. Sam Youkilis has been building a continuous archive of photographic works through his phone for the last six years. Working instinctively, Youkilis's short, immersive videos gather universal themes of human experience, using the casual language of the cameraphone to evoke something profound, anthropological, comprehensive and yet incomplete. Youkilis’s work springs from an attitude, a way of experiencing the world, that contains depth beyond the offhand ease in which his images freely circulate. In Youkilis’s first publication, the depth of this engagement with human patterns of behaviour is archived and scattered across a diverse range of themes, divided into chapters that playfully tease the tensions between categorisation and chance that inform his observational works. Made exclusively of video stills, Somewhere scours Youkilis’s database for images of everything from the time of day–7:07AM, 12:33PM—to unmade beds, the act of cutting, thresholds, dancing couples and gestures of romance. Presented as a dense 500-page sequence, Somewhere activates the archive and the typology as a source of human joy and communion while emboldening his subjects and unlocking the deep essence of different places worldwide. Youkilis embraces the real by engaging with both ephemerality and sincerity, while steeped in reverence for the photographic medium through a meticulous engagement with composition, colour, chiaroscuro and framing
Keywords: Youkilis, Sam -- 1993-; Geschichte 2017-2023; Fotografie; Bildband